A proteção da idade avançada no regime geral de previdência social - Siqueira, Thiago Barros de (2010)
The welfare of the elderly turns out to be one of the main challenges to be faced in this century, marked by an inexorable aging process of the population, which threatens the pursuit of dignity in old age, as the new social care requests of elderliness are not met. This study used mostly theoretical research and followed the deductive method, based on systematic analysis of law, in its constitutional and legal dimension. Based on several law doctrinal tendencies (Brazilian and foreign, especially Spanish authors) and statistics from authoritative national research institutes that define the new demands of the elderly, which must be met in order to obey the welfare ideal of the Constitution of 1988. Thus, we sought to assess the Brazilian social care, specifically the Social Security and to define the social risk that elderliness represent and also, starting from the constitutional ideal of inclusive and restorative social care, we sought to examine the social security benefits up to the new requirements of the elderly population